ATB-346, a novel hydrogen sulfide-releasing anti-inflammatory drug, induces apoptosis of human melanoma cells and inhibits melanoma development in vivo. (December 2016) - De Cicco, Paola; Panza, Elisabetta; Ercolano, Giuseppe; Armogida, Chiara; Sessa, Giuseppe; Pirozzi, Giuseppe; Cirino, Giuseppe; Wallace, John L.; Ianaro, Angela
Graphical abstract: Abstract: Inflammation plays a key role in tumor promotion and development. Indeed, cyclooxygenase-2 (COX-2) expression is strongly associated with different types of cancer. An emerging class of compounds with significant anti-inflammatory properties is the hydrogen sulfide-releasing non-steroidal anti-inflammatory drugs (H2 S-NSAIDs). They consist of a traditional NSAID to which an H2 S-releasing moiety is covalently attached. We have recently demonstrated that H2 S donors inhibit melanoma cell proliferation. In the current study, we evaluated the potential beneficial effects of a new H2 S-releasing derivative of naproxen, ATB-346 [2-(6-methoxynapthalen-2-yl)-propionic acid 4-thiocarbamoyl phenyl ester] which inhibits COX activity but also releases H2 S. We used cell culture and a mouse melanoma model to evaluate the effect of ATB-346 on: i) in vitro growth of human melanoma cells; ii) in vivo melanoma development in mice. Cell culture studies demonstrated that ATB-346 reduced the in vitro proliferation of human melanoma cells and this effect was associated to induction of apoptosis and inhibition of NF-κB activation. Moreover, ATB-346 had novel Akt signaling inhibitory properties. Daily oral dosing of ATB-346 (43 μmol/kg) significantly reduced melanoma development in vivo. This study shows that ATB-346, a novel H2 S-NSAID, inhibits human melanoma cell proliferation by inhibiting pro-survival pathways associated with NF-κB and Akt activation. Furthermore, oral treatment with ATB-346 inhibits melanoma growth in mice. In conclusion, the combination of inhibition of cyclooxygenase and delivery of H2 S by ATB-346 may offer a promising alternative to existing therapies for melanoma.